1997
DOI: 10.1046/j.1365-2168.1997.02459.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison of physical performance following laparoscopic and open inguinal hernia repair

Abstract: Laparoscopic hernia repair results in a quicker recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…In the present study the functional test after 1 week showed significantly less impairment in the laparoscopic group. Similar results were obtained by Berndsen et al 8 , and also by Liem et al 24 who compared curled sit-up and straight leg raising at 1 and 6 weeks after surgery.…”
Section: Discussionsupporting
confidence: 79%
“…In the present study the functional test after 1 week showed significantly less impairment in the laparoscopic group. Similar results were obtained by Berndsen et al 8 , and also by Liem et al 24 who compared curled sit-up and straight leg raising at 1 and 6 weeks after surgery.…”
Section: Discussionsupporting
confidence: 79%
“…9 Straight leg raising and activities of daily living questionnaires have been used in other studies to assess physical performance following laparoscopic and open inguinal hernia repair. 2 In our elderly group of patients, assessment with voluntary straight leg raising was measured in the height from the horizontal rather than exercise testing since levels of preoperative fitness were likely to be poor. We found that there was no significant difference at day 7 following surgery, thus supporting the view that this type of hernia repair is associated with minimal postoperative pain and quick recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Complications related to laparoscopy, such as intestinal or vascular injury during trocar insertion, potential for adhesions, the need for general anesthesia, and increased cost, are potential downsides of laparoscopic repair. Prospective randomized trials have been performed showing advantages of laparoscopic repair for one or more of the above-cited parameters [23][24][25]. Larger randomized studies [26] have shown some benefit in terms of less pain and more rapid return to work, but the same authors have shown more recurrences and higher costs in the laparoscopic repair groups [27].…”
Section: Groin Herniasmentioning
confidence: 99%